Reducing routine group and save testing in emergency laparoscopic appendicectomy surgery: a quality improvement project assessing the triple bottom line - Dominic Furniss; Cyra Mackintosh; Emanuele Gammeri; Vrettos Ierodiakonou (BMJ Open Quality)
Introduction There is compelling evidence supporting the omission of routine group and save (G&S) testing pre-operatively in emergency laparoscopy where appendicitis is suspected. Most studies are retrospective; however, one study prospectively demonstrated safe application in laparoscopic cholecystectomies only. We sought to assess safety, cost, and environmental and social savings—the triple bottom line—of omitting routine G&S testing in laparoscopic appendicectomies, by undertaking a quality improvement project at a busy district general hospital.Methods All patients who underwent an emergency laparoscopy +/− appendicectomy, between 1 November 2020 and 31 October 2021, were retrospectively reviewed, and cross-referenced to haematological testing and blood product dispensation data. A cost of £15 was applied to processed G&S samples and £1.89 to rejected samples. A carbon cost of 1,066 g CO2 emissions (CO2e) was applied to all samples. We then prospectively undertook a 6-month pilot intervention to omit routine G&S testing in these cases. Patients from either cohort who required blood transfusions underwent a deep dive to identify risk factors.Results Pre-intervention, 281/392 (71.7%) of patients had valid G&S samples prior to their procedure and no patient required blood products during their episode. Post-intervention, 56/189 (29.1%) patients had valid G&S samples. One patient with chronic anaemia required a preoperative blood transfusion. Pre-intervention, G&S testing cost £22.24 and 1.7 kg CO2e per laparoscopy. Post-intervention, the cost reduced to £9.78 and 0.7 kg CO2e per laparoscopy. The intervention saved £5,021 and 353 kg CO2e, and our institution has adopted a selective approach, based on clinical risk, for these cases indefinitely.Conclusion Routine G&S testing in emergency laparoscopy +/− appendicectomy is unnecessary, costing money and time and producing carbon emissions. With effective communication of risk-mitigating factors, practice can shift from high to low rates of preoperative testing. There are further savings accessible by applying this method to other surgical procedures using a risk-based approach.